Leap Eccentric Connectivity Index of Subdivision Graphs - Ali Ghalavand; Shiladhar Pawar; Nandappa D. Soner (Journal of Mathematics)
The second degree of a vertex in a simple graph is defined as the number of its second neighbors. The leap eccentric connectivity index of a graph M, LξcM, is the sum of the product of the second degree and the eccentricity of every vertex in M. In this paper, some lower and upper bounds of LξcSM in terms of the numbers of vertices and edges, diameter, and the first Zagreb and third leap Zagreb indices are obtained. Also, the exact values of LξcSM for some well-known graphs are computed.